2021
DOI: 10.1017/s136898002100272x
|View full text |Cite
|
Sign up to set email alerts
|

On-campus food environment, purchase behaviours, preferences and opinions in a Norwegian university community

Abstract: Objective: To assess food environment at OsloMet, through the nutritional profile and processing level of available commercial foods and drinks; as well as to determine food purchasing behaviours, preferences and opinions on the food environment; in order to identify whether interventions on campus need to be conducted. Design: Cross-sectional descriptive study. Setting: Pilestredet and Kjeller campus of OsloMet (Norway). Participants: To analyse the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 52 publications
3
8
0
Order By: Relevance
“…The assessment results from this study are consistent with the literature demonstrating that university food environments lack an availability of healthy foods and promote the consumption of ultra-processed discretionary foods and beverages [29,32,40]. In particular, recent evaluations of campus food environments in Brazil, New Zealand, Norway and Canada suggest they generally do not support healthy eating [30,32,33,40,41]. Within Australia, an assessment of the healthiness of foods provided within food retail outlets across seven universities showed that the majority of food products were classified as unhealthy [29].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The assessment results from this study are consistent with the literature demonstrating that university food environments lack an availability of healthy foods and promote the consumption of ultra-processed discretionary foods and beverages [29,32,40]. In particular, recent evaluations of campus food environments in Brazil, New Zealand, Norway and Canada suggest they generally do not support healthy eating [30,32,33,40,41]. Within Australia, an assessment of the healthiness of foods provided within food retail outlets across seven universities showed that the majority of food products were classified as unhealthy [29].…”
Section: Discussionsupporting
confidence: 88%
“…To date, there have only been a small number of assessments of the healthiness of campus food environments [29][30][31][32][33]. None of these studies have comprehensively assessed the healthiness, equity and environmental sustainability of university food environments, and no detailed frameworks exist to guide policy and practice in the area.…”
Section: Introductionmentioning
confidence: 99%
“…Two studies performed detailed food environment audits to assess food outlets and vending machines on the products sold, while the remaining three studies employed relatively more subjective responses or collective descriptions for food environment evaluation. However, audit results were contradicting: Martinez-Perez et al ( 61 ) identified unhealthy food and beverage options including sweet snacks and sugar-sweetened drinks as significant components of solid food (58.5 %) and total drinks (23.5%), respectively. However, Roy et al ( 55 ) observed a higher number of “healthy” outlets (17.8%) suggesting that healthy food options were available on campus and were higher in density than less healthy ones (3.6%).…”
Section: Resultsmentioning
confidence: 99%
“…Such healthy food environment initiatives also appear to be popular, with 92% of all staff and visitors surveyed indicating their support [ 21 ]. Recent survey data suggest university students and staff are similarly supportive of healthy food environment policies and practices [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%